Detection Of Processing Model Basic Elements In Intellectual Analysis Of Flexible Processes Through Business Process Intelligence; The 9th International Forum on Strategic Techology (IFOST-2014), September 21-23, 2014, Cox's Bazar, Bangladesh; he 9th International Forum on Strategic Techology (IFOST-2014), September 21-23, 2014, Cox's Bazar, Bangladesh[proceedings] - Rudometkina M. N. Monika Nikolaevna (Information & Communication Technology, 2014)
Title screen